HUBUNGAN PENGALAMAN KERJA DAN SELEKSI TERHADAP KINERJA KARYAWAN: Studi Kasus PT. MAYORA INDAH TBK - Sihombing, Christina N.; Suciati, Suciati; Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2016)
The research was conducted at PT. Mayora Indah Tbk to determine the relationship of selection and work experience on employee performance of IT Application. The purpose of this study was to determine the relationship of the selection and performance of employees, labor relations experience and the performance of employees in the IT Application in PT. Mayora Indah Tbk. This research is descriptive-correlational by as many as 29 employees, and the data were analyzed using the analysis of Rank Spearman. The result of this study indicate that (1) there is a significant relationship between the selection and performance of employees of the IT Application PT. Mayora Indah Tbk. It showed with the obtained t (4.516) is greater than t table (2.052). (2) there is a significant relationship between work experience and employee performance of IT Application PT. Mayora Indah Tbk. It showed with the obtained t (8.605) is greater than t table (2.052). Based on the results, it can be concluded that the selection process in the company has been run efficiently and should be maintained as letters of reference checks, medical tests for each prospective employee and was hired because of their ability offer meets the necessary criteria. In terms of work experience need to be maintained as the mastery of the work that have helped to more easily understand the tasks given by the leader, do not waste time working with other activities and professional attitude always put in the work. For the performance of employees in the company is sound and should be maintained as the concentration in the works to obtain satisfactory results, it can work well without supervision from superiors and can complete the work on time.Keywords: selection, work experience, employee performance